A Single-Center Retrospective Study of the Impact of Thyroid Cancer on the Malignant Risk of Contralateral TI-RADS 3 and 4 Nodules - Huan Liu; Jun Jin; Qiao Chen; Zhongmin Li (International Journal of Endocrinology)
Background. The incidence of thyroid nodules increases in the general population. Similarly, we have also seen a dramatic increase in the number of thyroid surgeries. However, the mortality rate of thyroid cancer remained stable or even decreased. The purpose of our study was to investigate whether thyroid cancer affects the malignant risk of the contralateral TI-RADS 3 and 4 nodules. Methods. We conducted a retrospective cohort study in our institution for all thyroid procedures due to nodules from December 2018 to December 2019. All eligible patients were divided into the experimental group (bilateral nodules) and the control group (unilateral nodules) to assess whether the proportion of malignant nodules was different between the two groups. Multivariate logistic regression analysis was used to control potential confounding factors to investigate whether their differences were statistically significant. Results. A total of 330 patients underwent thyroid surgery, of whom 137 were eligible, including 84 in the experimental group and 53 in the control group. The proportion of malignant nodules was significantly different between the experimental group and the control group (29.8% versus 58.5%, unadjusted OR 0.30, 95% CI: 0.17–0.82, p=0.001). However, after controlling for potential confounding factors, including age (p=0.004), gender (p=0.775), and TI-RADS classification (p≤0.001), we found that the difference was not significant (adjusted OR 1.08, 95% CI: 0.39–3.01, p=0.886). Conclusion. There is no evidence that thyroid cancer affects the malignant risk of the contralateral TI-RADS 3 and 4 nodules. This study has been registered with the Chinese Clinical Trial Registry (clinical trial registration number: ChiCTR2000038611, registration time: September 26, 2020).